2022
DOI: 10.1111/ijfs.16159
|View full text |Cite
|
Sign up to set email alerts
|

Fermented coconut jelly as a probiotic vehicle, physicochemical and microbiology characterisation during an in vitro digestion

Abstract: Summary There is little information on the survival of probiotics in plant‐based foods after simulated gastric and intestinal conditions, likewise the microstructure arrangement in the no‐dairy fermented food. This work aimed to study if the agar–agar in a fermented coconut jelly confers protection to probiotics, phenolic and antioxidant compounds during in vitro digestion. Samples containing higher agar–agar amounts tend to retain (P < 0.05) antioxidant and phenolic compounds in their network better, even aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This is in accordance with Farinha et al, 2015 [50], who reports that to improve probiotic survival, prebiotic ingredients can be added to food preparations containing probiotic microbiota. Moreover, our results are in agreement with the report of other authors, who confirmed that the addition of agar-agar into fermented coconut jelly can improve probiotics' survivability, and phenolic and antioxidant compounds during in vitro digestion [51].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with Farinha et al, 2015 [50], who reports that to improve probiotic survival, prebiotic ingredients can be added to food preparations containing probiotic microbiota. Moreover, our results are in agreement with the report of other authors, who confirmed that the addition of agar-agar into fermented coconut jelly can improve probiotics' survivability, and phenolic and antioxidant compounds during in vitro digestion [51].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the results showed that agar-agar-based samples of jellies were best evaluated in terms of the texture-distinguishing feature, "compactness" (Figure 3a,b). Domínguez-Murillo and Urías-Silvas, 2023, suggested that the addition of 1% of agar to samples of coconut jellies presented the maximum hardness (p < 0.05), due to more bonding points and intermolecular interactions [51]. It can be concluded that inulin can be a good alternative for sucrose, which is in line with current food design trends.…”
Section: Discussionmentioning
confidence: 52%